Single enzyme direct biomineralization of ZnS, ZnxCd1−xS and ZnxCd1−xS–ZnS quantum confined nanocrystals. Issue 61 (7th August 2017) - Sadeghnejad, Abdolhamid; Lu, Li; Kiely, Christopher J.; Berger, Bryan W.; McIntosh, Steven
Abstract : ZnS, Zn x Cd1− x S, and Zn x Cd1− x S–ZnS quantum dots were synthesized in the aqueous phase at room temperature via biomineralization enabled by a single enzyme in solution. Abstract : Biomineralization is an intriguing route towards the low temperature, aqueous phase, green synthesis of inorganic functional nanomaterials. Herein we describe the biomineralization and optical properties of Zn x Cd1− x S and Zn x Cd1− x S–ZnS quantum confined nanocrystals that have potential application in optoelectronics. The reported biomineralization process is reduced to perhaps its simplest form wherein a single recombinant cystathionine γ-lyase (CSE) enzyme is responsible for catalyzing mineralization within an otherwise inert solution and plays a role in controlling the alloy composition. The biomineralized nanocrystals are sphalerite structured with average diameter below 3 nm. Biomineralization of a passivating ZnS shell on Zn0.73 Cd0.27 S core nanocrystals is achieved through subsequent addition of Zn precursor. This shell growth increases the photoluminescence quantum yield to 7% and increases the radiative decay time to 97.6 ns compared with 40.9 ns for the core materials.